1983
DOI: 10.1002/maco.19830341003
|View full text |Cite
|
Sign up to set email alerts
|

On the influence of cold work on the oxidation of some stainless steels

Abstract: Oxidation experiments, performed by means of light interference microscopy, give information of the initial oxidation on a microscopic scale. A thin oxide layer on the substrate gives rise to an interference colour, which is directly correlated to the thickness of this layer. It is shown that not all stainless steels react in the same way to the same pretreatments. The oxidation behaviour of drawn AISI 304 and AISI 321 is completely different from that of Incoloy 800 H, while the undeformed and recrystallized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

1984
1984
2009
2009

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 5 publications
0
4
1
Order By: Relevance
“…For Incoloy 800H a decrease in oxidation resistance with increasing cold work has been reported [22]. However, this influence has not been seen in this study -probably due to an increased number of defects created by the bombardment procedure.…”
Section: Influence Of Cold Workcontrasting
confidence: 60%
See 1 more Smart Citation
“…For Incoloy 800H a decrease in oxidation resistance with increasing cold work has been reported [22]. However, this influence has not been seen in this study -probably due to an increased number of defects created by the bombardment procedure.…”
Section: Influence Of Cold Workcontrasting
confidence: 60%
“…Due to cold work a phase transformation occurs in which some martensite formation takes place in the austenitic grains. The grain boundaries between the austenite and martensite grains show a very high diffusivity for Cr and Fe [21], explaining the increase of the oxidation resistance of AISI 304 as a result of cold work [1, 2,22].…”
Section: Influence Of Cold Workmentioning
confidence: 99%
“…Cold work, in particular, was found to be beneficial in the long term, increasing oxidation resistance in 304 stainless steels [26]. Langevoort's work showed a small influence of cold work on the oxidation behaviour of 304 stainless steel under atmospheric and ultrahigh-vacuum conditions [25][26][27].…”
Section: Influence Of Cold Work On Surface Oxidationmentioning
confidence: 97%
“…Langevoort et al 5 explained their results from optical microscopic measurements of AISI 304 at temperatures of 770-970 K with the formation of an a' martensite structure within the austenite matrix. This martensite structure was found to exhibit a high rate of diffusion for chromium, 7 which will lead to a very fast initial and a very slow subsequent oxidation, due to a protective Cr203 oxide layer.…”
Section: Discussionmentioning
confidence: 99%
“…Stevens 4 observed that annealed specimens showed a better oxidation resistance than cold worked ones. Langevoort et aL 5 reported an increase in oxidation resistance of AISI 304 and 321 in the temperature range 800-1000 K, but a decrease in oxidation resistance of Incoloy 800H after cold work. Stokkers et aL 6 observed an increase in oxidation rate after ion bombardment of stainless steel AISI 314.…”
Section: Introductionmentioning
confidence: 96%